The application of biopore infiltration holes as groundwater conservation efforts - Diana Irvindiaty Hendrawan; Melati Ferianita Fachrul; Astri Rinanti; Sih Andajani; Muhammad Raihan Raivaldi; Tsabita Juliandini Jiwanti; Isti Rahmandani; Eva Gracia (Community Empowerment, 2021)
The reduction in green open space causes its reduction in the surface that can absorb water into the ground in residential areas. An increase in the amount of wasted rainwater that is wasted due to the reduced rate of water infiltration into the soil will cause flooding in the rainy season and drought in the dry season. A solution is needed to absorb water into the soil. Trisakti University in collaboration with Cisalak Village and the Indonesian Water Partnership held the training and counseling on the application of Biopore Infiltration Holes to residents of RW 12. This Community Service activity supports the program target of making 100,000 LRBs in Depok City. The method used was counseling conducted online and offline. After the counseling activity, the team made 80 LRBs equipped with booklets and X-banners containing procedures for making LRBs.